Mindfulness and Fear of Missing Out in Final Year Undergraduate Students - Sa’id, Mochammad; Cessia Sukma Dewi, Dara (KnE Social Sciences, 2022)
Final year students often face difficulties such as working on repeated thesis revisions, getting relevant literature, length of feedback from supervisors, and limited research time. Those who use social media tend to experience Fear of Missing Out (FoMO) syndrome. This study aimed to investigate the relationship between mindfulness and FoMO in final year undergraduate students. This study used a correlational quantitative approach. Research participants consisted of 126 final year undergraduate students using purposive sampling. For data collection, two instruments were used: Mindfulness Scale (.847) and Fear of Missing Out Scale (.829). The data were analyzed using Pearson’s Product Moment Correlation. The results showed that there was a significant relationship between mindfulness and FoMO in final year students (Sig. .000 < .05). In addition, the direction of the relationship between the variables was negative (-.308), meaning that the relationship between the two variables was in negative correlation. This means that if the individual had a high state of mindfulness, the tendency to experience FoMO was low. In contrast, if the individual had a low state of mindfulness, then his/her tendency to experience FoMO was high. Keywords: mindfulness, fear of missing out, final year, undergraduate student, undergraduate thesis